COUNTERING CORRUPTION: A KEY TO MENA BANKING RESILIENCE - Douagi, Ben Mrad; Wyème, Fatma; Olfa, Chaouachi; Gharsellaoui, Mongi (International Journal of Allied Research in Economics (IJARE), 2023)
Corruption in the banking sector is a major problem that can have negative consequences for the economy. This paper reviews the literature on the impact of corruption on the banking sector, with a focus on the following areas: (1) the lending decisions of banks, (2) the riskiness of banks' portfolios, (3) the stability of the banking system, and (4) economic growth. The paper concludes that corruption has a negative impact on all of these areas, and that it can lead to financial crises